Copper encapsulated in grass-derived phytoliths: Characterization, dissolution properties and the relation of content to soil properties. (1st November 2019) - Tran, Thu T.T.; Nguyen, Thao T.; Nguyen, Van T.; Huynh, Huong T.H.; Nguyen, Thinh T.H.; Nguyen, Minh N.
Abstract: The formation of phytoliths as a result of the precipitation of Si in many Si-rich plant species is known to encapsulate organic matter. This work aims to examine the possible encapsulation of Cu in grass phytoliths in an orange growing area, where Cu-rich fungicides have been excessively applied. Batch experiments, in combination with SEM-EDS and microscopy, were conducted for the grass-derived phytoliths and phytoliths separated from soil, thus revealing their dissolution properties, morphotypes and contents, in relation to soil properties. By measuring the Cu release accompanying the dissolution of phytoliths by different extractants, especially an Na2 CO3 /HNO3 solution, it was revealed that Cu was encapsulated within the silica body of the phytolith. This sink of Cu in the grass can be cycled to serve as a new Cu source in soils. Phytolith contents in the soil were up to 17.7 g kg −1 and tended to accumulate in soil depths from 0 to 20 cm. A positive correlation was found for soil phytolith and phytCu contents and may be indicative of the role of phytoliths as an enhancer of Cu accumulation in soil. It would be worth developing suitable techniques for the determination of phytCu, because common extraction/digestion methods are not suited for evaluating this Cu pool. Highlights: Excessive use of fungicides leads to accumulation of Cu in orange growing soils. Cu assimilated from soil might be encapsulated within phytolith structure in grass. Phytolith encapsulated Cu (phytCu) is a new sink and source of Cu in soils. Release of phytCu is controlled by the destruction of phytolith.